A patient-led survey on information and communication needs of patients with metastatic breast cancer in Ireland and Northern Ireland (CTRIAL-IE 23–05) - Siobhan Gaynor; Yvonne O'Meara; Emer Mulvaney; Rachel J. Keogh; Catherine S. Weadick; Fran J. Duane; Ann Mc Brien; Helen Greally; Mary Jane O'Leary; Ieva Teiserskyte; Isabel Beristain; Jacinta Marron; et al. (Breast)
Introduction: Although treatment advances have improved survival rates for patients with metastatic breast cancer (MBC), patient expressed needs have not been evaluated in Ireland to date. Methods: A 76 item questionnaire was designed by the lead author and a cohort of 41 other MBC patients in collaboration with a multidisciplinary team. The online survey was publicised nationally on all media platforms. Results: 246 patients completed the survey between July and October 2023. Most patients were satisfied with the manner of disclosure of their diagnosis but 77 % wanted more prognostic information. Disparate information sources were used to provide support. Only 35 % of patients had access to their records, yet 99 % of patients without access desired to have it. The majority (83 %) of patients were amenable to earlier palliative care referral. The symptom burden of respondents was high, 87 % experienced mental health issues and 68 % of those with menopausal symptoms were dissatisfied with the support. These burdens were compounded by financial stress with 20 % of patient unable to meet monthly expenses and by time toxicity with 25 % attending emergency departments in the previous 6 months. Conclusion: Currently the needs of MBC patients in Ireland and Northern Ireland have many unmet needs. The routine early provision of palliative care, psycho-oncology, medical social worker and dedicated liaison nurse supports guided by national guidelines and education for healthcare professionals, integrated with living well with cancer clinics and a dedicated medically verified website would provide an ecosystem where MBC care could be optimised for patients and their families.